Propagação vegetativa de miniestacas de Cordia trichotoma em função de auxinas e épocas de coleta - Faganello, Luiz Roberto (2012)
It was developed a study on vegetative propagation on the rooting of Cordia trichotoma semi-woody in Summer and Fall of 2011. Therefore this study aimed to evaluate the effects of different concentrations of IBA (indolbutiric acetic) and NAA (naphthalene acetic) acids on the rooting and establishment of Cordia trichotoma semi-woody cuttings gathered from the sprout of Cordia trichotoma seedlings. To accomplish the objective of this study, two experiments were conducted. The first experiment considers the effect of different concentrations of IBA (Indolbutiric) and NAA (naphthalene acetic) acids on the rooting of Cordia trichotoma stem cutting gathered from the sprout of Cordia trichotoma seedlings produced by seeds, in February 2011, using micro sprinkler irrigation, eight times a day. Cordia trichotoma seedlings were produced by seeds constituting a miniclonal garden with subsequent pruning of the aerial part. Sprouts were harvested resulting in semi-woody cuttings with 12.0 cm long and 5.5 mm in diameter and a pair of leaves in the apical portion reduced in a half. The treatments consisted of fast immersion of the cuttings base in IBA and NAA acids in concentrations of 0, 2.000, 4.000, 6.000, 8.000 mg i.a. L-1 in a randomized block design with factorial arrangement 2 x 5. After 60 days of cutting, rooting percentage, roots number and length, sprouting percentage, the number of shoots and new leaves were evaluated as well as the survival and mortality. When there were differences, the averages were compared by F test at 5 % probability. For concentrations, it was used a polynomial regression analysis to 1 % by F test. The vegetal regulator IBA at a concentration of 8.000 mg L-1 showed higher cutting rootings. The cutting originated from seedlings produced by seeds must be better investigated as an alternative to the vegetative propagation of the species in Summer. The second experiment describes the effect of different concentrations of IBA (Indolbutiric acetic) and NAA (naphthalene acetic) acids on the rooting of stem cuttings gathered from the sprout of Cordia trichotoma seedlings in May 2011, produced by seeds using intermittent mist. Cordia trichotoma seedlings were produced by seeds constituting a miniclonal garden with subsequent pruning of the aerial part. Sprouts were harvested, from the pruning of the previous harvest, resulting in semi-woody cuttings with 12.0 cm long and 5.5 mm in diameter and a pair of leaves in the apical portion reduced in a half. The treatments consisted of fast immersion of the cuttings base in IBA and NAA acids in concentrations of 0, 2.000, 4.000, 6.000, 8.000 mg i.a. L-1 in a randomized block design with factorial arrangement 2 x 5. After 70 days of cutting, rooting percentage, roots number and length, sprouting percentage, the number of shoots and new leaves were evaluated as well as the survival and mortality. When there were differences, the averages were compared by F test at 5 % probability. For concentrations, it was used a polynomial regression analysis to 1 % by F test. The use of plant growth regulator IBA resulted in increased callus formation in cuttings. The cuttings originated from seedlings produced by seed must be further investigated as an alternative to vegetative propagation of the species for this time of year.